THE COMPARISON OF ENGLISH AND RUSSIAN COUNTABLE AND UNCOUNTABLE NOUNS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article will explore the differences and similarities between countable and uncountable nouns in English and Russian languages. It will discuss the rules for forming plurals, using articles and quantifiers, and exceptions to these rules. By comparing and contrasting the two languages, the article aims to help language learners understand and correctly use countable and uncountable nouns in both English and Russian.